Improving Teachers First Aid Skills for Managing School Injuries: A Quasi-Experimental Study in an Indonesian Elementary School - Devi, Nurul; Mardiyah, Siti; Fitriyani, Noor (P3M Universitas 'Aisyiyah Surakarta, 2025)
Background Injuries frequently occur within school environments, ranking as the second most common location for injury incidents due to unsafe conditions and limited first aid preparedness. Children aged 5–14 years exhibit a high prevalence of injuries, reaching 13% in school-related incidents. Teachers, as front-line responders, must possess adequate first aid knowledge and skills to manage common injuries—such as falls, bruises, nosebleeds, fainting, and seizures—before professional medical care is available. Objective This study aimed to assess the effectiveness of a first aid training program in improving teachers’ skills in managing school-related injuries. Methods A quantitative approach with a quasi-experimental design (pretest–posttest without a control group) was conducted among 49 teachers at Al Islam 3 Gebang Elementary School, Surakarta. Total sampling was used. Skill levels were assessed before and after the training using standardized evaluation tools. Results The Wilcoxon signed-rank test showed a statistically significant improvement in teachers’ first aid skills after the training intervention (p = 0.01; p < 0.05). Conclusion First aid training significantly enhanced teachers’ skills in managing injuries among school children. Continued collaboration between schools and health professionals is recommended to maintain and further develop these essential competencies.